Construction and evaluation of a serial album for the prevention of foot complications in diabetics - Izabel Cristina de Souza; Joyce da Silva Costa; Mayara Maria Silva da Cruz Alencar; Paloma Gabrielly Amorim Monteiro; Priscila de Souza Aquino; Régia Christina Moura Barbosa Castro (Universidade Federal do Ceará, 2021)
Objective: to describe the construction process and evaluate the evidence for content and appearance validity of a serial album for the prevention of foot complications in diabetics. Methods: methodological study of the construction of the educational material, according to the following steps: bibliographic survey; construction of the educational technology and validation of content and appearance by experts in diabetes and technical production. The judges were chosen by convenience, five for content and two for appearance. The Content Validation Index and the Suitability Assessment of Materials were applied. Results: the Content Validation Index showed agreement among judges, with a result ranging from 0.76 to 1.0. According to the score obtained in the Suitability Assessment of Materials, the material was considered adequate, with a percentage of44.5%. Conclusion: the serial album was considered valid for content and appearance and is suitable for clinical validation for use by health professionals in health education activities.